Effects of social distancing during the COVID-19 pandemic on cognitive function and mental health in woman older - Araújo, Joamira Pereira de; Brasiliano, Marlon Madeiro; Ribeiro, Victor Barbosa; Farias , Silvio Romero de Araújo; Freitas, Eduardo Domingos da Silva; Cirilo-Sousa, Maria do Socorro (Journal of Health & Biological Sciences, 2025)
Objective: investigate the effects of social distancing during the COVID-19 pandemic on the global cognitive function and mental health of elderly women. Methods: a cross-sectional study was conducted through a video call of forty elderly women. Scores of cognitive functions (global, memory, and executive function) and levels of mental health (anxiety, depression, and sleep quality) were assessed before and during (after four months) COVID-19 pandemic. Results: social distancing significantly decreased global cognitive function (MMSE: -0.8; 95% CI: -1.2; -0.2; P = 0.006) and memory (Verbal fluency: −0.9; 95% CI: −1.6; −0.0; P = 0.035). Regarding mental health, social distancing demonstrated increasing significant levels of anxiety (+2.0; 95% CI: 0.3; 3.7; P = 0.042). No significant between-moment differences were observed for other cognitive and mental health outcomes. Conclusion: the measures of social distancing during the COVID-19 pandemic have had a major impact on the cognitive and mental health of elderly women.